2020
DOI: 10.1186/s12944-020-01333-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fish oil supplement induces age-specific contractile and proteomic responses in muscles of male rats

Abstract: Background: Dietary fish oil (DFO) has been identified as a micronutrient supplement with the potential to improve musculoskeletal health in old age. Few data are available for effects of DFO on muscle contractility, despite the significant negative impact of muscle weakness on age-related health outcomes. Accordingly, the effects of a DFO intervention on the contractile function and proteomic profile of adult and aged in an animal model of aging were investigated. Methods: This preliminary study evaluated 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…There were 10 pre-clinical studies, including 3 cell experiments [ 14 , 17 , 40 ] and 7 animal studies [ 18 , 41 , 42 , 43 , 44 , 45 , 46 ]. Refer to Table 2 and Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There were 10 pre-clinical studies, including 3 cell experiments [ 14 , 17 , 40 ] and 7 animal studies [ 18 , 41 , 42 , 43 , 44 , 45 , 46 ]. Refer to Table 2 and Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…One study [ 43 ] used the senescence-accelerated SAMP8 mouse ( n = 51), two studies [ 18 , 46 ] used Wistar rats, and one used [ 44 ] Sprague Dawley rats. Five studies [ 18 , 41 , 43 , 45 , 46 ] had young mice or rats aged from 25 weeks to 8 months as positive control groups, and in the experimental group, elderly mice or rats had an age range from 15 months to 24 months. EPA [ 41 , 44 ], DHA [ 41 ], ClA [ 42 ], dietary fish oil [ 45 ], and olive leaf extracts [ 18 , 46 ] were used as interventions in the animal studies, and all fatty acids showed a positive effect on old mice or rats.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations